2020
DOI: 10.1056/nejmoa2008457
|View full text |Cite
|
Sign up to set email alerts
|

Presymptomatic SARS-CoV-2 Infections and Transmission in a Skilled Nursing Facility

Abstract: BACKGROUNDSevere acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can spread rapidly within skilled nursing facilities. After identification of a case of Covid-19 in a skilled nursing facility, we assessed transmission and evaluated the adequacy of symptom-based screening to identify infections in residents. METHODSWe conducted two serial point-prevalence surveys, 1 week apart, in which assenting residents of the facility underwent nasopharyngeal and oropharyngeal testing for SARS-CoV-2, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

115
2,196
20
53

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 2,060 publications
(2,434 citation statements)
references
References 15 publications
115
2,196
20
53
Order By: Relevance
“…In addition to this kinetics, we also study the correlations between the infectiousness we estimate and the average viral shedding (Figure 4A) and the chance of obtaining a positive culture (Figure 4B) that was calculated by combining data from two different works. 8,17 Both these correlations are very strong, with correlation coefficients 0.83 and 0.97, respectively and high significance.…”
Section: Resultsmentioning
confidence: 95%
“…In addition to this kinetics, we also study the correlations between the infectiousness we estimate and the average viral shedding (Figure 4A) and the chance of obtaining a positive culture (Figure 4B) that was calculated by combining data from two different works. 8,17 Both these correlations are very strong, with correlation coefficients 0.83 and 0.97, respectively and high significance.…”
Section: Resultsmentioning
confidence: 95%
“…Although symptom screening is important, an investigation of a COVID-19 outbreak in a skilled nursing facility found that approximately one half of cases identified through facilitywide testing were among asymptomatic and presymptomatic persons, who likely contributed to transmission (4). These data indicate that symptom screening alone is inadequate to promptly identify and isolate infected persons in congregate settings such as correctional and detention facilities.…”
Section: Resultsmentioning
confidence: 99%
“…The reported figures from official statistics as well as recent research show the widespread transmission of SARS-CoV-2 and the high lethality of COVID-19 in nursing home residents (Arons et al, 2020). Moreover, more than half of the residents with a positive COVID-19 diagnosis are asymptomatic at the time of testing.…”
Section: Outlook and Suggestions For The Futurementioning
confidence: 99%
“…These asymptomatic cases very likely contribute to the transmission of the virus. Therefore, broad and frequent testing of all nursing home residents and their caregivers is recommended (Arons et al, 2020;Centers for Disease Control and Prevention, 2020). In addition, sufficient personal protective equipment is needed for nursing home staff and also for relatives and friends of residents.…”
Section: Outlook and Suggestions For The Futurementioning
confidence: 99%